Transformation of Rat and Hamster Embryo Cells by Extracts of City Smog - Freeman, Aaron E. (1971)
Extracts of particulate matter from condensates of city air were tested for their ability to transform rat or hamster cell cultures. Uninfected rat embryo cultures were not transformed, but cultures chronically infected with Rauscher leukemia virus were transformed by benzpyrene or by extracts of city smog. The smog extracts were 600 times more active than pure benzpyrene as transforming agents. Hamster embryo cultures infected with hamster leukemia virus were equally as sensitive as leukemia-infected rat cultures to the transforming effects of smog; uninfected hamster cultures were also transformed, although tenfold higher doses of smog extract were required.